Revisiting fiscal sustainability: panel cointegration and structural breaks in OECD countries - António Afonso; Jo\~ao Tovar Jalles (European Central Bank (ECB), 2012)
We assess the sustainability of public finances in OECD countries, over the period 1970-2010, using unit root and cointegration analysis, both country and panel based, controlling for endogenous breaks. Results notably show: lack of cointegration – absence of sustainability – between government revenues and expenditures for most countries (except for Austria, Canada, France, Germany, Japan, Netherlands, Sweden, and UK); improvements of the primary balance after past worsening in debt ratios for Australia, Belgium, Germany, Ireland, Netherlands and the UK; Granger causality from government debt to the primary balance for 12 countries (suggesting the existence of Ricardian regimes). Overall, fiscal policy has been less sustainable for several countries, and panel data results corroborate the time-series findings.
Keywords: C32; E62; H62; H63; 330; breaks; causality; debt; fiscal regimes; FMOLS; Panel Cointegration; primary balance; stationarity